Time-Varying Tolls in a Dynamic Model of Road Traffic Congestion with Elastic Demand - Erik Verhoef (Tinbergen Institute, 1997)
In this paper, a dynamic model of road traffic congestion is presented, with an elastic overall demand for morning peak road usage, and with the congestion technology used being 'flow congestion'. It is demonstrated that in such a case, the optimal time-varying toll should include a 'flat', time-invariant component when road users share the same desired arrival time. This has important consequences for the design of optimal toll schemes in reality, because it implies that optimal tolls cannot be set if the regulator has no information on the road users' desired arrival times.
Keywords: 330; Straßenbenutzungsgebühr; Theorie